Characteristics of Sie Reuboh Supplemented with Different Combinations of Palm Vinegar (Arenga pinnata) and Kaffir Lime Leaves (Citrus hystrix) - Masyitah Masyitah; I. I. Arief; T. Suryati (Faculty of Animal Science, Bogor Agricultural University, 2017)
This research was aimed to analyze the characteristics of sie reuboh processed with the addition of palm vinegar and kaffir lime leaves with different concentrations to produce sie reuboh with a good quality and to maintain the stability of its quality during storage at room temperature. The research consisted of 2 stages. In the first stage, 4000 g of sie reuboh was treated with different doses of palm vinegar and kaffir lime leaves (0 mL and 0 g, 100 mL and 10 g, 120 mL and 20 g, and 140 mL and 30 g) for microbiological analysis. Sie reuboh with the best result of microbiological analysis was later used in Stage 2 to be stored at room temperature and was analyzed for its physical antioxidant activity, thiobarbituric acid reactive substance (TBARS), and microbiological analysis. The result showed that different levels of palm vinegar and kaffir lime leaves did not significantly affect the aw, pH, yield, and microbiological characteristics of the sie reuboh. Different ratios of palm vinegar and kaffir lime leaves significantly affected (P<0.05) the tenderness of sie reuboh. Sie reuboh without addition of palm vinegar and kaffir lime leaves showed a better tenderness than sie reuboh added with palm vinegar and kaffir lime leaves. The best treatment based on microbiological analysis was shown by treatment of sie reuboh with 120 mL of palm vinegar and 20 g of kaffir lime leaves and this sie reuboh was later used to test the stability of the sie reuboh when it was stored at room temperature. The results showed that sie reuboh produced by addition of 120 mL of palm vinegar and 20 g of kaffir lime leaves demonstrated antioxidant activity for inhibition of free radicals as was indicated by the stability of TBARS value during 9 days of storage at room temperature. This combination of treatment could also effectively stabilize the quality of sie reuboh, as indicated by a proper storability at maximum limit of total plate count and mold growth until 3 days of storage at room temperature.